Supercapitalism in the relation between the environmental licensing and the financing of electoral campaigns - Jeronymo, Alexandre Cosme José (Sustainability in Debate, 2017)
The paper identifies the limits into the environmental licensing, and approximates them of the corporate funding for the electoral political campaigns. This environment called “Supercapitalism” is permissive to convert the territory of democracy in the territory of economic groups and political class captured. This correlation involves the donation-loan of money for the campaign politics and its evolution to fix residence in the capture of State by economics groups. The mechanisms used for the recuperation of the donation-loan instrumentalize the environmental licensing public authorities. The construction of the paper consider indicators of distrust in the political class and political party, use academic work, studies of nongovernmental organizations, and information of the press when reveal episode of the incompletes environmental impacts studies, population displacement and indemnification derisory, and fraudulent public hearings. Concludes signaling that the donation-load entered politics, captures the political class, instrument the State and corrupt process that environmental licensing and environmental democracy.